Teacher Problems in Implementing IT-Based Learning Media at SDN - Mujiono Sang Putra; Yeni Rahmawati; Nur Islamiati; Hen Ardiansyah (STKIP Taman Siswa Bima, 2024)
Teachers at SDN 17 Kempo have not been able to apply innovative media, especially information technology-based media. This research aims to determine the problems faced by teachers in implementing IT-based learning media at SDN 17 Kempo. The research uses a qualitative description type approach. The research subjects consisted of 21 teachers at SDN 17 Kempo. The research instrument used questionnaires and unstructured interviews. Data collection techniques used questionnaires and interviews. The data analysis technique uses the Miles & Huberman method, namely: data reduction, data presentation, drawing conclusions/verification. The research results show that the problems faced by teachers in implementing IT-based learning media include: 1) aspects of teachers' ability and understanding in implementing IT-based learning media; 2) aspects of supporting facilities and infrastructure; and 3) aspects of the lack of effort made by teachers in IT-based learning media. However, despite these problems, SDN 17 Kempo teachers still have high motivation in implementing IT-based learning media.